Succeeding in Bioeconomy: Serbian Universities’ Blueprint - Mizdraković, Vule M; Kostić, Marija; Stanković, Jelena (Industrija, 2018)
The purpose of this paper is to provide insight into the level of integration of the bioeconomy concept in the study programmes and modules at Serbian higher education institutions. Bioeconomy is based on multidisciplinary approach, which consists of research, education and innovation. Bioeconomy must be initiated by the government, developed by research institutions, universities and cluster, and thoroughly implemented into existing and emerging industries. As educators, Serbian universities should play a key role in developing future professionals. Research has been conducted to determine if Serbian universities educate students in the fields relevant to the concept of bioeconomy. All accredited study programmes in academic year of 2017/2018, at all universities in the Republic of Serbia, have been analysed. The research included 17 universities, 152 departments, 481 study programmes, 705 modules and 43,360 courses. The modules within the study programmes were categorised as bioeconomy-based modules, non-bioeconomy-based modules with at least one bioeconomy-based course, and non-bioeconomy-based modules. The research shows that of the total number of modules, 43% include one or more bioeconomy-based courses. The share of such courses within modules ranges from 1% to 21% and differs among groups of scientific fields.